Three new species of the cutthroat eel genus Dysomma, with comments on the variation of D. taiwanense (Anguilliformes: Synaphobranchidae) - Ho, Hsuan-Ching; Tighe, Kenneth A. (Zootaxa, 2018)
Three new species of eels of the genus Dysomma are described from the western North Pacific Ocean off Taiwan. Dysomma formosa sp. nov., described from 34 specimens, differs from the congeners in having single row of 11–14 large compound teeth followed by 3–10 smaller teeth on lower jaw, 17–33 lateral-line pores, and 128–133 total vertebrae. Dysomma brachygnathos sp. nov., described from two specimens, differs from the congeners in the lack of a pectoral fin, having an anterior position of anus (preanal length 17.8–ca. 18.6% SL), 23–32 lateral line pores, a short lower jaw, and 131+‒136 total vertebrae. Dysomma robinsorum sp. nov., described from four specimens, differs from the congeners in having an anterior position of anus; preanal length 15.5–16.9% SL, no intermaxillary teeth; multiple rows of teeth on upper jaw; four compound teeth on vomer; teeth on lower jaw multiserial, those on inner row slightly enlarged, and 122–124 total vertebrae. Components of the variation of Dysomma taiwanense originally described from Taiwan are provided based on an additional 52 recently identified specimens.